69.7k views
1 vote
47 = 2(x + 3) + 3(x - 3)
what's the answer to this ?

2 Answers

3 votes
the answer should be x=10
User Zakir Sheikh
by
5.0k points
3 votes


47 = 2(x + 3) + 3(x - 3)


47 = 2x + 6 + 3x + - 9


47 =(2 x + 3x) + (6 + - 9)


47 = 5x + - 3


47 = 5x - 3


5x - 3 = 47


5x = 47 + 3


5x = 50


x = (50)/(10)


x = 10

Let us check whether or not we have found out the correct value of x by placing 10 in the place of x .

So :-


47 = 2(10 + 3) + 3(10 - 3)


47 = (20 + 6) + (30 - 9)


47 = 26 + 21


47 = 47

LHS = RHS

As the left hand side of the equation is equal to the right hand side of the equation , we have found out the correct value of x .

Therefore , 47 = 2 ( 10 + 3 ) + 3 ( 10 - 3 ) and x = 10 .

User Mbottone
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.